Wie wird die Bedingung formuliert? Eine Untersuchung zur sprachlichen Beschreibung von bedingten Wahrscheinlichkeiten (mathematica didactica, 2025)
This paper uses qualitative content analysis to develop a category system that systematically records the formulations of conditional probabilities from a linguistic perspective. A subsequent category-based text analysis of task texts from current textbooks reveals that the range of formulations used differs between the textbooks. In addition, linguistic expressions of N=77 high school graduates are examined with regard to typical errors in conditional probabilities. Implications for research and practice are discussed.